PENGARUH KEPRIBADIAN DAN KEMAMPUAN PEMECAHAN MASALAH TERHADAP KUALITAS KEPEMIMPINAN - Suryadi Suryadi; Luhur Wicaksono; Usman Radiana (Jurnal Visi Ilmu Pendidikan)
This study aims to determine the influence of personality and problem-solving ability on leadership quality. Through a quantitative correlational approach with a sample of teachers and principals in Singkawang City, it was found that aspects of personality referring to the five big personalities have a positive effect on leadership quality, but aspects of emotional stability are not significant on leadership quality. Aspects of problem-solving ability with creative problem-solving steps are significant on leadership quality. Personality and problem-solving ability simultaneously have a positive and significant effect on leadership quality. The importance of the concept of Asset-based thinking as an approach that focuses on the strengths possessed by leaders to achieve better leadership quality. Further research is expected to explore other aspects of leadership in more depth.